DESIGN OF TRUSSED SUPPORTING STRUCTURE FOR THE LIGHT-SMALL OFF-AXIS THREE-MIRROR REFLECTIVE SPACE CAMERA - XI JiaLi; ZHANG Lei; YANG Lin; XIE Peng (Jixie qiangdu)
A trussed supporting structure with carbon fiber trusses and titanium frames was designed to meet the requirements on precision and mass of a light-small off-axis three-mirror reflective space camera. After analyzing the common forms of the supporting structure for space cameras,a method of the supporting structure with the secondary mirror and the folding mirror fixed separately was determined according to the structure characteristics of this optical system. A dynamic size optimization was conducted to lighten the structure and improve the stiffness of this structure. After the size optimization the finite element analysis and vibration experiments were conducted. It shows that the supporting structure could satisfy the requirements on precision and mass of this camera,and the fundamental frequency reaches 291.4Hz under the condition that the mass of this trussed supporting structure is not more than 4Kg. The design scheme of this trussed supporting structure could provide some references to the other light-small space cameras with the same type.